Sustainable Development through Corporate Social Responsibility: A case study of Cochin Shipyard Ltd. - Nimmy A. George and Manoj Edward
Sustainable development has become the core objective of any business activity. United Nations has introduced Sustainable Development Goals (SDGs) in 2016 with the objective of transforming the entire nations into a sustainable economy by 2030. CSR is found to be an effective vehicle for sustainable development ( Moon, 2007). The government of India took the initiative to include the sustainable development projects such as Swachh Bharat and Skill India under Schedule VII (specifying thematic areas for CSR) of Indian Companies Act 2013. As a result, companies in India are participating more actively in the sustainable development of the country. Hence, under the new mandatory CSR rule, the Cochin Shipyard Ltd, a Mini Ratna CPSE listed company has strategised their CSR activities towards sustainable development. This paper analyses the CSR activities of Cochin Shipyard through case study methodology. The primary information about the CSR activities and its implementation strategy was collected through the interviews, with the Head of CSR and Managers in charge of CSR Cell. Secondary Data was collected from the Annual Report, newsletters of Cochin Shipyard Ltd, the website of Cochin Shipyard Limited, previous relevant studies and UN reports and website. The study reveals that the constant and stable efforts for CSR implementation enhances the sustainability of the business and inclusive growth of the society and thereby contributes to achieve the sustainable development goals by 2030. The different strategies and approaches of Cochin Shipyard Ltd for the implementation of CSR Projects are discussed.